1996
DOI: 10.1038/bjc.1996.453
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer drug characterisation using a human cell line panel representing defined types of drug resistance

Abstract: Summary Differential drug response in a human cell line panel representing defined types of cytotoxic drug resistance was measured using the non-clonogenic fluorometric microculture cytotoxicity assay (FMCA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…In the present study, we studied the gene expression and drug activity in a panel of 10 cell lines representing different mechanisms of anticancer drug resistance. Previous studies have shown that drug activity patterns in this panel can be used to classify anticancer drugs according to mechanism of action (Dhar et al, 1996). Here we showed that this classification also corresponded to identifiable patterns of gene expression and that the genes which correlated to drug sensitivity and resistance seem to be biologically relevant.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In the present study, we studied the gene expression and drug activity in a panel of 10 cell lines representing different mechanisms of anticancer drug resistance. Previous studies have shown that drug activity patterns in this panel can be used to classify anticancer drugs according to mechanism of action (Dhar et al, 1996). Here we showed that this classification also corresponded to identifiable patterns of gene expression and that the genes which correlated to drug sensitivity and resistance seem to be biologically relevant.…”
Section: Discussionsupporting
confidence: 62%
“…The human cancer cell line panel has been described previously (Dhar et al, 1996). The panel consists of the parental cell lines RPMI 8226 (myeloma), CCRF-CEM (leukaemia), U937-GTB (lymphoma) and NCI-H69 (small-cell lung cancer); the drugresistant sublines 8226/Dox40 8226/LR5, CEM/VM-1, U937/vcr, H69AR and the primary resistant ACHN (renal adenocarcinoma).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…by Dahr and co-workers. 3 Thus, sensitivity profiles of novel drugs with unknown mechanism of action can be compared to profiles of known drugs to formulate hypotheses on their mechanisms of action as well as be used to identify important structural characteristics by computing whether drugs with similar activity also have similar structural features.…”
Section: Introductionmentioning
confidence: 99%